Association between screen time, physical activity and sleep quality among youths - Liu, Gang; Liu, Duan (International Journal of Public Health Science (IJPHS), 2023)
To reduce the risk of contracting COVID-19 during the outbreak, the use of portable smart terminals (PST) among youths has increased significantly because youths prefer playing on their PST indoors. Hence, this article aims to study the impact of PST on youths’ sleep quality and the effect of walking on improving sleep quality during the COVID-19 pandemic. A survey was conducted on the daily walking steps, sleep quality, and the use of PST among 312 ordinary youths aged 18-25. The control group kept their original lifestyle, while the experimental group walked 10,000 steps a day for 30 days. This study found that 88% of the respondents used PST for more than four hours. Also, the detection rate of sleep disorders among youths accounted for 39% of the total respondents. Compared to the control group, the sleep duration and quality of youths in the exercise group significantly improved (p<0.05). In conclusion, youths spend more time on PST and less time on physical activities, which worsens their sleep quality. Thus, by appropriately increasing their daily steps, the adverse effects of PST can be reduced, and the sleep quality of youths can be improved.